Efficient accumulation of new irregular monoterpene malonyl glucosides in Nicotiana benthamiana achieved by co-expression of isoprenyl diphosphate synthases and substrate-producing enzymes - Gerasymenko, Iryna; Sheludko, Yuriy V.; Schmidts, Volker; Warzecha, Heribert (Frontiers in Plant Science, 2025)
Irregular monoterpenes have limited natural sources but possess unique activities applicable in medicine and agriculture. To enable sustainable plant-based production of these compounds, we established a transient expression procedure to enhance the biosynthetic flux in Nicotiana benthamiana toward dimethylallyl diphosphate (DMAPP), a substrate for isopentenyl diphosphate synthases (IDSs) that generate irregular monoterpene skeletons. Considering the benefits of glycosylation for accumulating and storing monoterpenes in extractable form, we focused on developing a platform for the production of non-volatile glycosylated irregular monoterpenes using three IDS that form branched and cyclic structures. The analysis of methanolic leaf extracts from transiently transformed N. benthamiana plants revealed six major new components, 6-O-malonyl-β-D-glucopyranoside and 6-O-malonyl-β-D-glucopyranosyl-(1→2)-β-D-glucopyranoside derivatives of chrysanthemol, lavandulol and cyclolavandulol, five of which are novel compounds. Alleviating two bottlenecks in the DMAPP formation in plastids by co-expressing 1-deoxyxylulose 5-phosphate synthase and isopentenyl diphosphate isomerases increased the yield of chrysantemyl and lavandulyl glucosides produced by plant-derived IDS to 1.7 ± 0.4 μmol g-1 FW and 1.4 ± 0.3 μmol g-1 FW, respectively. A bacterial cyclolavandulyl diphosphate synthase operated efficiently in chloroplasts and cytoplasm. The highest irregular monoterpene concentrations were achieved in cytoplasm by co-expression of hydroxymethylglutaryl-CoA reductase, the bottleneck enzyme of the mevalonate pathway for DMAPP biosynthesis. The mean level of cyclolavandulyl glucosides reached 3.9 ± 1.5 μmol g-1 FW; the top-performing plants contained 6.6 μmol g-1 FW. This yield represents the highest amount of irregular monoterpenes produced in plant systems.